Recognizing and Overcoming Challenges of Couple Interview Research. (October 2013) - Mellor, Ruth M.; Slaymaker, Emma; Cleland, John
In this article we discuss some methodological and ethical challenges we faced when conducting a couple-based study on men's role in contraceptive switching, and how we overcame them. The challenges we discuss include recruiting couples with a range of experiences, ensuring informed consent of participants, maintaining confidentiality within interviews, and participants discussing interview content between interviews. As appropriate, we have drawn on study participants' views of these challenges. We conclude that although couple research poses challenges, they can be overcome or minimized, and that for certain research questions this methodology is well worth using.